Cloud-based global online marketplaces review on trust and security - Ghazali, Osman; Yang Leow, Chun; Qaiser, Shahzad; Pattabiraman, Nanthini; Vasuthevan, Sathiyaroobaa; Abdusalam, Eman Mohamed; M. Barakat, Mustafa (2019)
Customer disposition to data, nature of the information on site, protection concerns, trust, security concerns, and the notoriety of organization efficaciously affect the trust of Internet shoppers in the site. Two noteworthy and basic issues for e-commerce sites and consumers are trust as well as security. A belief that someone is good and honest and will not harm you, or something is safe and reliable is called trust; while security is an attempt to safeguard the data from unauthorized access. Information security is a vital management as well as technical requirement over the internet for effective and secure payment transaction activities. The safety of e-commerce resources from use, destruction, unauthorized access and alteration is known as E-commerce security so there is an urgent need to study its dimensions such as authenticity, integrity, availability, privacy, confidentiality and non-repudiation. This paper reports a review of four popular online marketplaces which are Alibaba, Amazon, eBay andTaoBao as case study on two main criteria namely building trust among users and ensuring security on the platform. Furthermore, we discuss the methods being used by each online marketplace to build trust and their unique way ofimproving the security. Finally, different ways of building trust and technique to ensure the security is presented in a tabular form for each online marketplace.